2017
DOI: 10.13102/rscdauefs.v0i0.1658
|View full text |Cite
|
Sign up to set email alerts
|

Mortalidade Infantil Por Doença Falciforme Na Bahia: Um Estudo Epidemiológico

Abstract: Descrever o perfil epidemiológico dos óbitos infantis por transtorno falciforme na Bahia em crianças menores de um ano de vida, nos anos de 2008 a 2013, registrados no Sistema de Informações sobre Mortalidade. Métodos: Trata-se de um estudo exploratório, transversal de cunho epidemiológico, baseado em dados de óbitos infantis por transtornos falciformes nos anos de 2008 a 2013, obtidos no Sistema de Informações sobre Mortalidade, com o acesso ao DATASUS, (e) analisados por meio da estatística descritiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
1
3
0
3
Order By: Relevance
“… 4 The high SCD fatality rate was emphasized in a mortality study on children under one year old in Bahia from 2008 to 2013. 5 A study aiming to describe the mortality of women of childbearing age with sickle cell disease, using national data from 2010 to 2015 in Brazil, determined the need to improve the contraceptive care to reduce the female mortality in the population. 6 The first Brazilian study at a single institution in Rio de Janeiro found the overall fatality rate of 16.77% among patients with sickle cell anemia and concluded that mortality rates for children and adults were higher than those reported in developed countries of the northern hemisphere.…”
Section: Introductionmentioning
confidence: 99%
“… 4 The high SCD fatality rate was emphasized in a mortality study on children under one year old in Bahia from 2008 to 2013. 5 A study aiming to describe the mortality of women of childbearing age with sickle cell disease, using national data from 2010 to 2015 in Brazil, determined the need to improve the contraceptive care to reduce the female mortality in the population. 6 The first Brazilian study at a single institution in Rio de Janeiro found the overall fatality rate of 16.77% among patients with sickle cell anemia and concluded that mortality rates for children and adults were higher than those reported in developed countries of the northern hemisphere.…”
Section: Introductionmentioning
confidence: 99%
“…It is undeniable that L-glutamine can bring survival benefits to patients with SCD by balancing the NAD + /NADH ratio 59,60 to decrease CVOs in patients with SCDD 51 . It is known that the survival of patients with SCD in first-world countries such as the USA and England can reach ages over 60 years which cannot be compared with data from some national studies in Brazilian capitals that indicate that the median mortality would be around 30 years [61][62][63] .…”
Section: Discussionmentioning
confidence: 99%
“…Nesse estudo percebeu-se preponderância na cor/raça parda, conforme encontrado também em outros estudos epidemiológicos da DF (RAMOS et al, 2017). A cor/raça na Doença falciforme reflete a origem histórica que a doença carrega, pois a doença originouse no continente africano podendo também ser encontrada em diversas populações do mundo.…”
Section: Discussionunclassified